Optical-resonator-based biosensing systems: current status and future prospects - Nordin, Anis Nurashikin (Dove Medical Press Ltd, 2016)
Optofluidic devices have emerged as a promising label-free method for sensitive detection of biological molecules. Its advantages of rapid analysis, high specificity, and low interactions with samples have made it a popular device for biological and chemical analyses. This mini review describes state-of-the-art optofluidic devices based on optical resonators for biosensing. Advanced optical resonator geometries such as microspheres, microrings, and their integration with fluidics have been described. It is predicted that to meet demands of disease diagnostics for multiple clinically relevant samples, sizes of optical resonators will shrink further and geometries that enable multiplexing and integration with signal processing will be the trend of the future.